Medication adherence beliefs of community-dwelling hypertensive African Americans - Lewis, Lisa M; Askie, Pheobe; Randleman, Shirley; Shelton-Dunston, Brenda (The Journal of cardiovascular nursing, 2010)
Medication adherence is low among hypertensive patients regardless of ethnic background. However, the prevalence of nonadherence is higher among African Americans when compared with their white American counterparts. Recognizing African American perspectives about their adherence to antihypertensive medications is necessary for the development of successful interventions aimed at improving adherence to prescribed regimens. The purpose of this qualitative study was to explore community-dwelling hypertensive African American behavioral, normative, and control beliefs regarding their adherence to antihypertensive medications. A community and academic partnership was formed to conduct 3 audio-taped focus groups with 40 hypertensive and low-income African American adults aged 18 years and older. Interview questions were based on the theory of planned behavior. All transcripts from the tapes were analyzed using thematic analysis. Behavioral beliefs associated with medication adherence identified both positive and negative outcomes. Family, friends, neighbors, and God were associated with normative beliefs. Limited financial resources, neighborhood violence, and distrust of healthcare professionals were key control beliefs. Although these results cannot be generalized, they do provide significant insight into the contextual factors associated with the lives of community-dwelling hypertensive African Americans who fit a similar demographic profile. These findings are important because they can be used to tailor interventions to increase their medication adherence.